Den'gi i politika . Den'gi i politika . Money and Politics . Деньги и политика - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Economic and political developments in Russia after the attempted coup d'état of August 1991; copyright protection. Featured in the program: Astaf'ev, Mikhail Georgievich (Politician) Contributors: Vasil'ev, Aleksandr (Anchor) Экономическое и политическое развитие России с момента августовского путча в августе 1991 года; проблема защиты авторских прав. В программе участвуют: Астафьев, Михаил Георгиевич (Политик) Создатели: Васильев, Александр (Ведущий/Ведущая)